Intensive Care Unit-Specific Virtual Reality for Psychological Recovery After ICU Treatment for COVID-19; A Brief Case Report - Vlake, Johan H.; van Bommel, Jasper; Hellemons, Merel E.; Wils, Evert-Jan; Gommers, Diederik; van Genderen, Michel E. (Frontiers in Medicine, 2021)
A substantial number of ICU survivors are expected due to the SARS-CoV-2 outbreak, who are at risk for psychological impairments, such as post-traumatic stress disorder, anxiety and depression. We designed a COVID-19 intensive care unit-specific virtual reality (ICU-VR) intervention and tested it on one of our COVID-19 patients. The impact of event scale-revised and the hospital anxiety and depression scale showed that this patient suffered from PTSD, anxiety, and depression on the day of the intervention. One week after receiving ICU-VR, levels of PTSD, anxiety and depression had normalized, and stayed normalized until 6 months after discharge. In conclusion, innovative technologies, such as VR, have the potential to improve psychological rehabilitation, and should therefore be considered by clinicians for the treatment of ICU-related psychological sequelae after COVID-19.